Application of remotely sensed satellite data to identify Skipjack Tuna distributions and abundance in the coastal waters of Bone Gulf. (March 2019) - Putri, ARS; Zainuddin, M
Abstract: Skipjack tuna is a typical tropical tuna species with very large potential, so that it becomes the main target among Bone Gulf fishermen. Oceanographic factor anomalies have an impact on the distribution and abundance of skipjack tuna. This study aimed to analyze the relationship between satellite data of Sea Surface Temperature (SST) and Chlorophyll-a (chl-a) anomalies and, skipjack tuna catch and distribution. Using the remote sensing data from May to August 2012-2018, we analyzed the SST and chl-a anomalies. The oceanographic and skipjack tuna Catch per Unit Effort (CPUE) data, we identified their relationship using the Generalized Additive Model (GAM). The results of this study indicated that positive and negative anomalies have occurred where SST ranging from -0.8 – 0.6 °C and, chl-a ranging from -0.06 – 0.08 mg m-3 during the study period. We found that the anomalies of both oceanographic factors influenced a shift in the distribution pattern of Skipjack tuna in the coastal waters of Bone Gulf. The SST and chl-a anomalies were statistically significant factors affecting skipjack tuna abundance. This study suggests that these variables play an important role in developing tuna fisheries management and conservation.